Sensitivity in Callus Tissue of Plectranthus amboinicus (L.) through Mutation Induction with Colchicine - Syarifah Iis Aisyah; Sri Suhesti; Kunto Wibisono; Waras Nurcholis (AGRIVITA, Journal of Agricultural Science, 2022)
Mutation induction by colchicine is one method to improve plant genetic diversity (polyploidy). This study aims to 1) obtain growth regulators composition suitable in inducing callus, 2) obtain the LC50 value in callus of P. amboinicus, 3) to determine the effect of colchicine on callus growth, 4) to get shoots (putative mutant) varian, regenerating from indirect organogenesis (callus) in MV1. The study is conducted at the Laboratory of Agricultural Seed Management, Plantation Research, and Development Center from June 2018 to June 2019. The study uses a complete randomized design with four treatments and three replications. Explants use ware the nodes. Callus induction uses MS0 medium with 0.5 ppm 2.4-D, 2 ppm 2.4-D, 0.5 ppm 2.4-D + 1 ppm BAP, and 0.5 ppm 2.4-D + 0.5 ppm TDZ treatment. Mutation induction was performed using colchicine concentration at 0%, 0.02%, 0.04%, and 0.06% treatments. The regeneration media is an MS0 medium. The results show the best combination of plant growth regulators to induce the callus is 0.5 ppm 2.4-D. The LC50 colchicine concentration is at 0.0275%. However, this phenotype is reversible. An additional subculture period is required to move to normal morphology